Poetry in Motion, 1933-1966 [float] - Cal Poly San Luis Obispo Audio-Visual Department::::::::: (1965)
Two men and two women drive a buggy pulling a float with the Poly P on it. Behind that is an open book with the years 1933 written on the left page and 1966 on the right page. The book has a model rocket coming out of it. The side of the float reads 'Poetry in Motion'.